Synthesis, Characterization And Catalytic Studies Of Nanocrystalline Cs-Abw Zeolite In Henry Reaction Of Benzaldehyde And Nitroalkanes - Ghrear, Tamara Mahmoud Ali (2020)
Zeolite Cs-ABW is an 8-membered ring pore aluminosilicate zeolite (diameter of 3.4 × 3.8 Å2) that is rarely reported in its application due to its dangerous crystallization condition using high temperature and pressure (695 °C, 1000 bar). In this work, zeolite Cs-ABW nanocrystals have been hydrothermally synthesized without using any harmful organic template. The zeolite nanocrystals with very high solid yield (81. 88%) can be obtained within 60 min and at 180 C (~20 atm); a condition which is much faster and gentle than the existing synthesis methods.